2012
DOI: 10.1177/0886260512447578
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Violence Scale

Abstract: Youth violence represents a serious problem affecting individuals, communities, and the larger society. Greater efforts aimed at the eradication of youth violence are necessary, and work in this field could be enhanced by psychometrically strong measures. The present study examined the factor structure of the Attitudes Toward Violence Scale (ATV) using exploratory factor analysis (EFA) with a sample of 359 high school students. A three-factor structure was identified. The three factors were invariant across se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Response choices are as follows: Very much disagree = 1, Mostly disagree = 2, Slightly disagree = 3, Neither agree nor disagree = 4, Slightly agree = 5, Mostly agree = 6, and Very much agree = 7. A recent study (Davidson & Canivez, 2012) reported a Cronbach's alpha of .88. In this study, the Cronbach's alpha coefficient was .80.…”
Section: Attitudes Toward Partner Violencementioning
confidence: 98%
See 1 more Smart Citation
“…Response choices are as follows: Very much disagree = 1, Mostly disagree = 2, Slightly disagree = 3, Neither agree nor disagree = 4, Slightly agree = 5, Mostly agree = 6, and Very much agree = 7. A recent study (Davidson & Canivez, 2012) reported a Cronbach's alpha of .88. In this study, the Cronbach's alpha coefficient was .80.…”
Section: Attitudes Toward Partner Violencementioning
confidence: 98%
“…The subscale Attitudes Toward Partner Violence (PV) in the General Attitudes Toward Violence (ATV; Davidson & Canivez, 2012;Lonsway & Fitzgerald, 1995) was used to measure attitudes toward partner violence. The subscale comprises four items describing physical violence in intimate relationships in the form of hitting and slapping.…”
Section: Attitudes Toward Partner Violencementioning
confidence: 99%
“…Six items from the Attitude towards Violence (ATV) scale (Lonsway & Fitzgerald, 1995), abbreviated by Davidson and Canivez (2012), were adapted to measure participants' support for Muslim military violence. The participants were asked to indicate their level of agreement with statements such as, "Muslim nations should be ready with a strong military at all times."…”
Section: Support For Muslim Military Violencementioning
confidence: 99%
“…The participants were asked to indicate their level of agreement with statements such as, "Muslim nations should be ready with a strong military at all times." Responses were scored on a 1 (strongly disagree) to 7 (strongly agree) rating scale as used by Davidson & Canivez (2012). The 6items scale did not achieve measurement invariance (see SOM).…”
Section: Support For Muslim Military Violencementioning
confidence: 99%
“…It is noted that "youth violence is a complex social problem," including violence between coevals, as well as between dating partners, and between groups (Davidson & Canivez, 2012). Thus, a number of risk factors for violence among young people have been described in foreign literature and include a history of violent victimization (Latham et al, 2019), antisocial beliefs and attitudes, exposure to violence and conflict in the family and society (Farrington et al, 2017).…”
Section: Introductionmentioning
confidence: 99%